Theme-Rheme Pattern: Its Contribution to Cohesion and Coherence in The Students’ Research Background - Suharsono, Suharsono; Ashadi, Ashadi; Feri, Zefki Okta (REiLA : Journal of Research and Innovation in Language, 2024)
Cohesion and coherence are pivotal aspects of academic writing. Although the analysis of these elements in academic texts has garnered considerable attention from researchers worldwide, there remains a notable paucity of studies focused on the research backgrounds of student texts, particularly with respect to their educational level. This study sought to explore how the effective utilization of Theme-Rheme structures can enhance the overall clarity and organization of students’ research backgrounds. Employing a qualitative content analysis approach inspired by Krippendorff (2004), this study meticulously scrutinizes fifty samples of academic papers to discern the prevalence and variations of Theme-Rheme patterns and their impact on the logical flow of information. The thematic structure formulated by Halliday & Matthiessen (2004/2014) and the thematic progression framework by Bloor & Bloor (2004) were instrumental in analyzing the data. The findings reveal that students utilize a variety of theme types in their research backgrounds. The unmarked theme is the most prevalent, accounting for 55% in undergraduate theses (UT), 54% in master's theses (MT), and 59% in doctoral dissertations (DD). Following this, the textual theme is utilized at rates of 30% in UT, 34% in MT, and 31% in DD. The marked theme appears less frequently, comprising about 13% in UT, 11% in MT, and 8% in DD, while the interpersonal theme is rarely employed, with an approximate usage of 2% across all educational levels. This study sheds light on the significance of Theme-Rheme structures in academic writing and offers valuable insights for educators and students alike, who are striving to enhance the quality of their academic papers.